PO.1.20 Prognostic biomarkers of organ damage in patients with newly diagnosed SLE. (27th September 2022) - Enocsson, H; Jönsen, A; Bengtsson, AA; Eloranta, M; Svenungsson, E; Gunnarsson, I; Rönnblom, L; Leonard, D; Sjöwall, C
Abstract : Purpose: The urokinase plasminogen activator receptor (uPAR) is expressed on various cell types and is involved in proteolysis, migration and adhesion. A soluble form (suPAR) is yielded at shedding and has emerged as a severity biomarker in malignancies, inflammatory and infectious diseases. 1 Previously, high levels of suPAR at systemic lupus erythematosus (SLE) diagnosis was shown to associate with future organ damage in an international SLE cohort. 2 Herein, the aim was to confirm suPAR as a prognostic biomarker of organ damage in well-characterized Swedish patients with recent-onset SLE and to compare its prognostic value with other proteins detected in blood. Methods: Serum samples from 274 newly diagnosed (<6 months) SLE patients from four Swedish referral centers (Linköping, Lund, Stockholm, Uppsala) were analyzed for suPAR (ELISA; Virogates, Denmark) and for 184 potential biomarkers (Inflammation and Organ damage panel, Olink, Sweden). Protein levels were related to organ damage development as defined by the Systemic Lupus International Collaborating Clinics/American College of Rheumatology damage index (SDI). Clinical follow up-data have so far been extracted for 210 of the patients. Results: A total number of 38 patients (18%) had accrued organ damage before the 1-year follow-up, 75 patients (37%) had developed damage after 3 years, and 88 patients (47%) after 5 years. In addition to suPAR, 9 proteins differed significantly (p<0.01, Mann-Whitney) between patients with SDI≥1 and without damage (SDI=0) at both the 3- and 5-year follow-up. The top three significant proteins (p<0.001 at the 3-year follow-up) were G protein-coupled receptor 56 (GPR56), interleukin-18 receptor 1 (IL-18R1) and carbonic anhydrase 14 (CA14) of which the latter was decreased among patients who developed organ damage. Conclusions: The accumulation of organ damage is tightly associated with morbidity and mortality in patients with SLE. The biomarker suPAR, already validated for clinical triaging in acute care settings, could identify patients early who have a high risk to develop organ damage. These patients are thus in need of intensified follow-up. Additional data extraction and analysis will clarify the potentials of suPAR, GPR56, IL-18R1, CA14 and other proteins to predict development of organ damage, facilitate risk stratification, guide follow-up intensity, and provide tailored pharmacotherapy in SLE. References: Rasmussen LJH, Petersen JEV, Eugen-Olsen J. Soluble Urokinase Plasminogen Activator Receptor (suPAR) as a Biomarker of Systemic Chronic Inflammation. Frontiers in immunology. 2021;12 :780641. Enocsson H, Wirestam L, Dahle C, Padyukov L, Jonsen A, Urowitz MB, et al. Soluble urokinase plasminogen activator receptor (suPAR) levels predict damage accrual in patients with recent-onset systemic lupus erythematosus. Journal of autoimmunity. 2020;106 :102340.